Extração e caracterização de nanocristais de celulose a partir de folhas de abacaxi - Santos, Roni Marcos dos (2013)
The pineapple leaf (PL) is an agricultural waste with annual output and available in abundance, whereas in 2011 were produced about three million tons, being rarely used and currently has a low commercial value. Therefore, this agro-waste deserves to be better and/or properly used. The aim of this study was to explore PL as a source of raw material for the production of cellulose nanocrystals (CN). The CN were extracted by acid hydrolysis at 45°C for 5, 30 and 60 minutes, using 20 mL of H2SO4 (9.17 M) for each gram of material. The resulting CN were characterized by crystallinity index, morphology (shape and size) and thermal stability. Among the hydrolysis conditions carried out, the best extraction time was 30 minutes, with yield of 65%. At this extraction time, the CN presented a needle-shaped nature, high thermal stability (225 °C) when compared to the thermoplastic processing temperature (about 200 °C), high crystallinity (87.3%) relative to other sources CN cellulosic derived from agricultural residues (e.g., soy hull 73.5%), an average length of 249.7 ± 51.5 nm and a diameter of 4.45 ±1.41 nm, giving an aspect ratio (L/D) of around 60. Therefore, CN obtained from PL has great potential as reinforcement in the manufacture of nanocomposites. The production of CN from this underutilized agro-waste has commercial application potential that can add value to the pineapple cultivation, generate extra income for farmers and also help in agribusiness diversification. In addition, the reuse of these residues allows a significant reduction in both the volume of waste accumulated in the environment and in the extraction of raw materials, which is against the concept of sustainable development.